(untitled) (Research, Society and Development, 2021)
Diabetes Mellitus (DM) is one of the main health challenges of the 21st century, as it is a silent disease with great potential for poor evolution if not properly treated. Therefore, it is important that the population is aware of this pathology and takes the necessary measures before it worsens in order to maintain health. Likewise, it is essential that health professionals know how to conduct efficient and effective care to the population, both focused on prevention and health promotion, as well as on the treatment and maintenance of health. Aiming to promote multiprofessional discussion groups on diabetes care for patients in Basic Health Units (UBS) and professionals from two units of Family Health Strategies (ESF) in a city in the interior of Minas Gerais and to verify if the discussion groups promote changes in self-care behavior with DM. The meetings were attended by 57 users and 10 health professionals, discussing what diabetes is, its complications, psychological problems and diabetic diet. A workshop was held and with the doubts raised, videos and informational materials were created. The DM self-care assessment was performed using the Diabetes Self-Care Activity Questionnaire - QAD, but we did not obtain a significant result of participation adherence, with 9 initial responses and 3 after the workshops. As a result, there was an improvement in the relationship between users and professionals of the ESFs, greater knowledge of users about their disease and self-care, enabling students to have an interprofessional experience.